Fishing boats at anchor near Fisherman's Wharf - Albert Walton DeRome:::Creator::::::::::::
Large purse seiners, lamparas, possibly feluccas, and lighters at anchor, probably at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)